Unmet Needs of Surgical Care for Children: A Case Study in the Brazilian Publicly-Financed Health System - Bressan-Neto, Mario; Filezio, Marina Rosa; Ferri-de-Barros, Fabio; Defino, Helton Luiz Aparecido (Revista Brasileira de Ortopedia, 2021)
Objective To measure and document the clinical impact of the waiting time for surgical treatment of patients with spinal deformities in a quaternary center in Brazil.Methods In total, 59 patients with spinal deformity waiting for surgery on our hospital's list were evaluated to observe the impact of the waiting time on the progression of the deformity. Patient evaluation was performed using the SRS-22r questionnaire for health-related quality of life (HRQL) and radiographic images to evaluate the deformity of the spine at the time the patients were included in the waiting list and at the most recent appointment. The radiographic parameters selected for comparison were: Cobb angle of the primary and secondary curves, coronal alignment, apical vertebral translation, pelvic obliquity, sagittal vertebral axis, kyphosis (T5-T12), and lordosis (L1-S1).Results Low HRQL scores according to the SRS-22r questionnaire were observed in patients waiting for surgery. The radiographic parameters showed progression of the deformity on the initial evaluation when compared with the most recent follow-up evaluation.Conclusion The patients waiting for surgical treatment of spinal deformities in our center showed relatively low HRQL scores and radiographic progression of the deformity.
Keywords: spine; scoliosis; waiting list; vertebral curvatures; health policy